The Marketing Mix Factors Affecting Purchasing Decisions for Non-animals Testing Cosmetic and Skincare Products. (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
This study has an objective to examine the impact of marketing mix factors on purchasing decisions of non-animalstestingcosmetic and skincare products on students and employees at HEG University, Switzerland. This research is descriptivecausative research aims to find the influence of an independent variable that is in this research is product, price, promotion anddistribution to dependent variable that is purchase decision. The number of samples is 68 respondents.Analytical techniqueused is mean and standard deviation. The study revealed that Product and Promotion were extremely important factorsaffecting consumer purchasing decision. And then Place about cosmetic retail stores and Price respectively. On the other hand,marketing factors that respondents gave the least importance is Product about packaging. The respondents gave neutralimportant at this point. For the content and motivation in communicating and convincing consumers of cosmetic companiesand organizations that banned animals testing found that most respondents purchase cosmetic and skincare products once amonth. They agreed that cosmetic and skincare companies that prohibit animal testing have a better image than the cosmeticand skincare company that used animals-testing. And also, it is not necessary to experiment on animals for cosmetic industrybecause nowadays there are many volunteers who willing to experiment and have the lab to grow artificial human skin forcosmetics and skincare testing. Moreover, non-animal test logo on cosmetic and skincare products were reliabilities andaffecting the consumer purchasing decision. And most respondents tend to have intention to purchase cosmetic and skincareproducts that are non-animals testing.